Taṭwīr ʾAdawāt Ikhtibār Taʿlīm al-Ṣarf al-Muʿtamidah ʿalá Niẓām ʾAndrūyd: Dirāsah Taṭbīqīyah ʿalá Ṭalābat Maʿhad Dār al-Najāh al-ʾIslāmī - Silviya, Arina (Alsina : Journal of Arabic Studies, 2024)
Technological advancements have become vital in enhancing Arabic language education, particularly in assessing Arabic morphology learning at the Pondok Pesantren Daarun Najaah, where traditional methods lack innovation. This study develops "Kuis Shorof," an Android-based interactive assessment tool, driven by a needs analysis revealing the demand for digital media to improve student comprehension. Designed using Android Studio, the application includes 125 questions (35 multiple-choice, 35 true/false, 30 matching, 25 arranging) sourced from the Naẓm al-Maqṣūd textbook, featuring a user interface with cover pages, instructions, and results. Validation yielded a validity of 0.67 and reliability of 0.72, with questions rated "good" and "easy/medium," supported by expert evaluations (87% media, 95% content). Tested on 5 then 25 students, it achieved ratings of 83.73% and 88.64% ("very good"), with scores rising from 74.6 to 84.3 (13%) at statistical significance (t = -7.580, p < 0.05) and time efficiency (grading reduced to 5 minutes). Despite its benefits (interactivity, accessibility), limitations such as the absence of immediate feedback and a faulty back button necessitate improvements. Future enhancements, including AI integration, could broaden its educational impact.